-5x-3(-3x-4)=56

Simple and best practice solution for -5x-3(-3x-4)=56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-3(-3x-4)=56 equation:


-5x-3(-3x-4)=56

We simplify the equation to the form, which is simple to understand
-5x-3(-3x-4)=56

Reorder the terms in parentheses
-5x+(+9x+12)=56

Remove unnecessary parentheses
-5x+9x+12=+56

We move all terms containing x to the left and all other terms to the right.
-5x+9x=+56-12

We simplify left and right side of the equation.
+4x=+44

We divide both sides of the equation by 4 to get x.
x=11

See similar equations:

| 5x+2=7(x+1)-x | | 180=5x+11+119 | | -6=-31+m | | 660x(1-15x)=0 | | 0.7w+16+4w=27.38 | | 4n^2-6n+6=0 | | -6+10n=-76 | | -4x+6(2x-12)=24 | | 119=5x+11 | | 4x+-5=10-2 | | 45x=550 | | 6x+9-8(x+1)=3x+4 | | -14=23x | | 13+13x=-481 | | 7x/8-3x/8=1 | | 3n+4-n=12+n | | 6x-4(-4x+3)=186 | | 6+1/4(32x-8x)=27 | | -7x+5(6x-4)=-158 | | 60x=550 | | 6x-1=63 | | -x-6y=30 | | -2x+3(-7x+17)=-133 | | 200m-125m+43,425=45,000-150m | | 6x-7(-3x+4)=188 | | (2x+20)+(6x+24)=180 | | 9y-2(y-6)=3(2y+4) | | -12a+10=-62 | | -2x+7(3x+18)=-102 | | 30x-20=15x-12 | | 2(3x-7)+x=4-6x | | 80+9t=7t |

Equations solver categories